Modernisation of the constitutional status of the individual in the light of constitutional reforms - Maslovskaya, Tatiana S.; Plyugina, Inna V. (Journal of the Belarusian State University. Law, 2021)
The constitutional reforms carried out to some extent in recent years in many states largely affect various aspects of the organisation and functioning of public authorities, affect the content of the constitutional status of an individual, changing the established scope of rights, freedoms and duties, as well as often expanding the guarantees of protection of rights and freedoms, including in relation to certain categories of the population (children, youth, etc.). In many cases, we can talk about expanding the value catalog, filling it with new provisions that reflect modern democratic achievements, as well as determining the parameters of further state development, building relations between the state and society. It can be stated that at present the limits of the realisation of individual human and civil rights and freedoms are changing, in particular, under the influence of scientific and technological progress. It is obvious that these issues require additional scientific understanding, the search for scientifically based solutions that allow for a balance of public and private interests, the harmonisation of traditional values and modern realities. Based on the generalisation of the experience of constitutional transformations of foreign countries, the article highlights the directions of modernisation of the constitutional status of the individual, while focusing on the experience of the Russian Federation and the Republic of Belarus.